Participatory seed exchange (PSE): A community based mechanism for promoting access to seeds - Pudasaini, Niranjan; Ghimire, Krishna Hari; Gurung, Rita; Pitambar, Shrestha; Gauchan, Devendra (NAGRC, 2020)
Participatory Seed Exchange (PSE) is a low cost, simple and effective community-based mechanism for improving farmers' access to locally adapted seeds and planting materials which promotes farmer led on-farm conservation and utilization of the agrobiodiversity by exchanging available Agricultural Plant Genetic Resource (APGR) within the community (Shrestha et al 2013, Gautam et al 2017, Sthapit et al 2019). In Nepal, PSE was first piloted by the Western Terai Landscape Complex Project (WTLCP) in 2008 (Shrestha et al 2013). PSE is being utilized as a multi-propose tool to identify, exchange and document available APGR along with associated traditional knowledge by mobilizing local community and their networks. Though PSE is a one-day event, it takes an approximately a month-long time period to plan, prepare and practice.